ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETERLAMBATAN RUJUKAN PADA KASUS KEGAWATDARURATAN MATERNAL DI WILAYAH KERJA PUSKESMAS - Miftahul Khairoh; Arkha Rosyaria Badrus (Rena Cipta Mandiri, 2026)
Background: Maternal emergencies require immediate management to prevent maternal and fetal morbidity and mortality. Delays in referral remain one of the major factors contributing to adverse maternal outcomes. Several factors, including maternal and family knowledge, family decision-making, transportation availability, and distance to referral facilities, are suspected to contribute to referral delays. Objective: This study aimed to analyze factors associated with referral delays in maternal emergency cases within the working area of Pasean Primary Health Center, Pamekasan. Methods: This study employed a quantitative analytical design with a cross-sectional approach. A total of 40 respondents were selected using a total sampling technique. Independent variables included maternal/family knowledge of pregnancy danger signs, family decision-making, transportation availability, and distance to referral facilities. The dependent variable was referral delay. Data were analyzed using the Chi-Square test with a significance level of α = 0.05. Results: The results showed that most respondents had poor knowledge (55.0%), delayed family decision-making (57.5%), long distances to referral facilities (60.0%), and experienced referral delays (57.5%). Statistical analysis revealed significant associations between knowledge and referral delay (p = 0.008), family decision-making and referral delay (p = 0.003), transportation availability and referral delay (p = 0.021), and distance to referral facilities and referral delay (p = 0.010). Family decision-making was identified as the most strongly associated factor. Conclusion: Knowledge, family decision-making, transportation availability, and distance to referral facilities were significantly associated with referral delays in maternal emergency cases. Strengthening health education, improving family preparedness, and optimizing the referral system are essential to reduce delays in maternal emergency management.